Macroeconomic and Bank-Specific Factors Affecting Islamic Bank Profitability in Indonesia - Syah, Toufan Aldian (Islamicate Institute, 2022)
This study examines how macroeconomic and bank-specific variables influence the profitability of Islamic Commercial Banks in Indonesia. Using qualitative-documentary analysis, the research integrates both internal performance metrics—such as capital adequacy, cost efficiency, and credit quality—and external macroeconomic indicators including GDP growth and inflation. Framed by the Resource-Based View and Financial Intermediation Theory, the study finds that profitability is most sustainable when internal capabilities are strategically aligned with macroeconomic stability. Inflation and GDP growth significantly impact bank earnings, while internal variables such as capital structure and operational efficiency remain critical performance drivers. The findings reveal that profitability is a dynamic outcome of both internal governance and environmental conditions. This research advances existing literature by providing a holistic framework for assessing Islamic bank performance and offers practical implications for policymakers and bank managers seeking to improve financial resilience within a sharia-compliant context.